2004
DOI: 10.1007/s00210-004-0958-x
|View full text |Cite
|
Sign up to set email alerts
|

Repeated administration of the 5-HT1B receptor antagonist SB-224289 blocks the desensitisation of 5-HT1B autoreceptors induced by fluoxetine in rat frontal cortex

Abstract: Desensitisation of 5-HT(1A) and 5-HT(1B) autoreceptors is thought to be the mechanism underlying the therapeutic effects of fluoxetine and other selective serotonin re-uptake inhibitors (SSRIs) when these are administered chronically, while blockade of these autoreceptors occurring on administration of an SSRI together with an autoreceptor antagonist is responsible for the acute increase in 5-HT levels in vivo observed under these circumstances. The effects of repeated administration of SSRIs together with 5-H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…This has been previously demonstrated in guinea pigs in both frontal cortex and dentate gyrus (Roberts et al 2000), and we demonstrate here that 21 days paroxetine treatment produced an augmented SSRI-induced effect in the rat frontal cortex (when compared to an acute administration). Chronic SSRI treatment has been demonstrated to produce a functional desensitization of 5-HT 1A (Chaput et al 1986;Blier et al 1987;Le Poul et al 1995; and also possibly 5-HT 1B receptors (Shalom et al 2004), although the data for the latter are contradictory (Gobbi et al 1997; for review on both receptors see Hjorth et al 2000). Thus, co-administration of 5-HT 1A/B receptor antagonists (either as separate molecules or as a single molecule such as SB-649915-B) prevents this need for desensitization (Hervas et al 2001;Dawson et al , 2002 and, thus, produces acute increases in forebrain 5-HT.…”
Section: Discussionmentioning
confidence: 98%
“…This has been previously demonstrated in guinea pigs in both frontal cortex and dentate gyrus (Roberts et al 2000), and we demonstrate here that 21 days paroxetine treatment produced an augmented SSRI-induced effect in the rat frontal cortex (when compared to an acute administration). Chronic SSRI treatment has been demonstrated to produce a functional desensitization of 5-HT 1A (Chaput et al 1986;Blier et al 1987;Le Poul et al 1995; and also possibly 5-HT 1B receptors (Shalom et al 2004), although the data for the latter are contradictory (Gobbi et al 1997; for review on both receptors see Hjorth et al 2000). Thus, co-administration of 5-HT 1A/B receptor antagonists (either as separate molecules or as a single molecule such as SB-649915-B) prevents this need for desensitization (Hervas et al 2001;Dawson et al , 2002 and, thus, produces acute increases in forebrain 5-HT.…”
Section: Discussionmentioning
confidence: 98%
“…There is also evidence that 5-HT 1B receptor desensitization is seen following chronic SSRI treatment indicating that these receptors may play a part in mediating the effects seen with SSRIs (Blier and Bouchard, 1994;Newman et al, 2004;Shalom et al, 2004). Preclinical microdialysis studies have demonstrated that the selective 5-HT 1B receptor antagonist SB-224289 augments the 5-HT increase seen with paroxetine, and that WAY100635 further potentiates this effect (Roberts et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…This elevated level of 5-HT, in turn, stimulates 5-HT receptors to initiate a cascade of effects and relieve the symptoms of repetitive behaviors. However, the elevated 5-HT level also stimulates inhibitory autoreceptors (5-HT 1B/1D ) which by definition, regulate the release of 5-HT in an inhibitory manner and negatively affect the mode of action of SSRIs [5,6]. It is, thus, anticipated that coadministration of SSRIs with 5-HT 1B/1D receptor antagonists to be advantageous over SSRIs alone with respect to the magnitude of extracellular brain 5-HT levels produced [7][8][9].…”
Section: Background and Significancementioning
confidence: 99%